2020
DOI: 10.3390/jcm9124078
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Troponin Elevation in COVID-19 Hospitalized Patients

Abstract: (1) Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) penetrates the respiratory epithelium through angiotensin-converting enzyme-2 (ACE2) binding. Myocardial and endothelial expression of ACE2 could account for the growing body of reported evidence of myocardial injury in severe forms of Human Coronavirus Disease 2019 (COVID-19). We aimed to provide insight into the impact of troponin (hsTnI) elevation on SARS-CoV-2 outcomes in patients hospitalized for COVID-19. (2) Methods: This was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Acute myocardial injury, caused by myocardial infarction or myocardial inflammation, is associated with increased serum levels of hsTn. A very recent study indicated that a rise in hsTnI was an independent predictor for mortality in COVID-19 patients, with a four-fold increase in the risk of death (OR: 3.84 (95%CI: 1.78–8.28)) [ 74 ].…”
Section: Biomarkers Associated With Worse Prognosis In Covid-19 Patients Suffering Acute Coronary Syndromesmentioning
confidence: 99%
“…Acute myocardial injury, caused by myocardial infarction or myocardial inflammation, is associated with increased serum levels of hsTn. A very recent study indicated that a rise in hsTnI was an independent predictor for mortality in COVID-19 patients, with a four-fold increase in the risk of death (OR: 3.84 (95%CI: 1.78–8.28)) [ 74 ].…”
Section: Biomarkers Associated With Worse Prognosis In Covid-19 Patients Suffering Acute Coronary Syndromesmentioning
confidence: 99%
“…One study showed that 41 (22%) of admitted patients had myocardial injury and the mortality was similar among those with myocardial injury regardless of whether they had or did not have COVID-19 infection [47]. The included studies also examined the relationship between troponin level and mortality or the prevalence of elevated cardiac enzymes among hospitalized COVID-19 patients [35,39,41,44,51,52,54,58,61,66].…”
Section: N Resultsmentioning
confidence: 99%
“…Despite the detection of myocardial injury based on troponin elevation has been an established risk factor in critical COVID-19 patient [ 24 ], this diagnosis based on LV dysfunction by cardiac ultrasound is not a consensus. In a prospective multicenter survey, including 1216 patients, 38% of COVID-19 patients presented LV impairment in the hospital setting [ 25 ] and a systematic review showed that most COVID-19 myocarditis has reduced LVEF [ 26 ].…”
Section: Discussionmentioning
confidence: 99%